P18.06.B ETS-Transcription Factor inhibitors are effective inTERT promoter mutated meningioma cells in vitro. (5th September 2022) - Neumayer, K; Kastler, L; Laaber, M; Roschger, C; Lenz, S; Lötsch-Gojo, D; Berger, W; Gruber, A; Spiegl-Kreinecker, S
Abstract: Background: TERT promoter mutations in meningiomas were recently found to be strongly prognostic and associated with malignant progression and risk of recurrence. As result, the mutation in the TERT promoter generates a binding site for E twenty-six (ETS) transcription factors. Consequently, ETS-transcription factor inhibition might represent a novel strategy to impede meningioma growth. In a prior study we could demonstrate effectiveness of the ETS-transcription factor inhibitor YK-4-279 in TERT promoter mutant meningiomas. Recently, TK216 the clinical derivative of YK-4-279 was developed. Therefore, we aimed to clarify whether TK216 might have an increased effect as compared to YK-4-279 in TERT promoter mutated meningioma cells in vitro. Methods: A meningioma-derived cell line (BTL695) generated from a TERT promoter mutated (C228T) anaplastic meningioma served as cell model for the experiments. BTL695 was characterized by high telomerase activity and TERT mRNA expression as analysed by the TRAP assay and RT-PCR, respectively. Genomic aberrations were verified using Ion Torrent Oncomine Comprehensive Assay v3-based next-generation sequencing (NGS). The sensitivity of BTL695 to YK-4-279 and TK216 was determined using an MTT-based viability assay (EZ4U). To elucidate the effectiveness of TK216 on cell cycle and apoptosis, cells were stained with PI and annexin V, respectively, and measured by flow cytometry. The effect of TK216 on the protein expression of the cleaved poly(ADP-ribose) polymerase-1 (PARP-1), indicative for apoptosis, was investigated by western blot. Additionally, a TK216-resistant cell model (BTL695res) was generated and analysed by NGS. Results: BTL695 was significantly more sensitive to TK216 as compared to YK-4-279 (p<0.0001) characterized by the distinctly lower IC50 value of TK216 exposed cells (0.7 µM TK216; 1.6 µM YK-4-279). Flow cytometry analysis revealed a TK216 induced G2M cell cycle arrest and increased apoptosis rate, which was additionally verified by the expression of cleaved PARP-1 expression using western blot. Genomic aberrations were found in 18 genes including NF2, CDKN2A/B, ARID1A and PTEN. Interestingly, although the majority of genomic alterations was persistent in the TK216 resistant cell model, a p53 mutation was newly acquired as compared to the parental cell line. Conclusion: In summary, our results indicate that ETS transcription factor inhibition by TK216 exerts antitumour activity in our TERT promoter mutant meningioma cell model. Additionally, the sensitivity against TK216 is superior to YK-4-279 and therefore TK216 may represent a promising new therapeutic option for patients with aggressive, TERT promoter mutated meningioma.